Assessment of the Prognostic Power of Preoperative Laboratory Biomarkers in Predicting Pediatric Complicated Appendicitis and the Outcomes of the Relevant Surgical Intervention - Canan Salman Önemli; Kübra Evren Şahin; Özge Atacan (Galenos Yayinevi, 2023)
Aim:The purpose of this study was to assess the prognostic power of preoperative laboratory biomarkers in pediatric age group individuals diagnosed with appendicitis in the emergency department in distinguishing complicated appendicitis from non-complicated appendicitis and in predicting postoperative outcomes.Materials and Methods:The population of this descriptive, cross-sectional, retrospective study consisted of children (younger than 18 years of age) who applied to our hospital's emergency department between January, 2020 and October, 2021 and underwent surgical intervention with a diagnosis of acute appendicitis. Preoperative laboratory test results, intraoperative surgical outcomes, lengths of hospital stay and postoperative complications data were recorded in the patient follow-up forms and analyzed.Results:The intraoperative and pathological data revealed that 179 (37.8%) and 294 (62.1%) patients had complicated and non-complicated appendicitis, respectively. An analysis of the complete blood count results indicated that the C-reactive protein (CRP) level, and CRP-to-albumin ratio (CAR), neutrophil count, leukocyte count, monocyte-to-lymphocyte ratio (MLR), and neutrophil-to-lymphocyte ratio (NLR) were significantly higher, whereas the sodium and albumin levels were significantly lower in those patients with complicated appendicitis than in those with non-complicated appendicitis. Among the parameters investigated, the NLR, CAR values, and the presence of hyponatremia were found to be significantly associated with the length of hospital stay and postoperative complication rates in those patients with complicated appendicitis.Conclusion:The findings of our study show that leukocyte counts, neutrophil counts, NLR values, CRP, sodium, and direct bilirubin levels meas-ured preoperatively in the emergency department can be used to identify pediatric patients with complicated appendicitis. In addition, MLR and CAR values, as new biomarkers, can provide guidance in emergency interventions and also predict postoperative outcomes.